Sosialisasi Pentingnya Konsumsi Susu Kedelai Sebagai Minuman Sehat, Kaya Protein, Dan Serat Serta Alami Untuk Anak Sekolah Dasar Di Kecamatan Ubud Kabupaten Gianyar - I Made Suarjana; I A Eka Padmiari; PP Sri Sugiani (Jurnal Pengabmas Masyarakat Sehat, 2019)
Increasing public awareness of the importance of milk for the fulfillment of nutrients in an effort to realize health life, encouraging people to get used to consuming milk including soy milk. The socialization of the importance of consuming milk for school-age children shows the participation of Denpasar Polytechnic institutions to participate in efforts to improve public health. The community service activities with the theme of socializing the importance of consumption of soy milk as a healthy drink, rich in protein and fiber and natural, aims to increase students' knowledge about nutrition, especially instilling a positive perception of the importance of consuming soy milk. This activity was held at SD 3 Sayan and SD 3 Singakerta, Ubud District, Gianyar Regency. The target number of 155 people with participants' ages is 9-10 years old. Submission of health messages using media images, games, and demonstrations that are easy to understand. Activities are only limited to efforts to increase knowledge and attitude but have not yet reached an effort to measure the impact widely in the community. At least children have experience gained from demonstrations given. Statistically, the effect of socialization has succeeded in increasing students' knowledge and attitudes. This is known by looking at the comparison of students' knowledge and attitudes before and after socialization. The implementation of the activity went smoothly by obtaining support from the school, including the enthusiasm of students in participating in the activity. In the future, this activity is expected to be carried out in a sustainable manner as a program of activities to increase public awareness in improving health statusKeywords: socialization, soy milk, school children